Parametric Sail Analysis of Sailing Yachts in 9-20 Meters - Sari, Sarih; Aydin, Muhsin (CHAMBER MARINE ENGINEERS, 2019)
The study was carried out in order to determine the dimensions of the sailing parameters for the sailing yachts in the most appropriate way and to estimate the performance values for the determined sail and boat. The length overall range, which is widely used for this purpose, is determined between 9 and 20 m. In order to make calculations and estimations in this range, 3 boats having 9.15, 14.25 and 19.50 m full size were formed. 81 different sailing equipment was created to correspond to each boat. For each boat and sailing equipment, it was examined at wind speeds of 6, 12 and 20 knots and in angles of 45, 90 and 110 degrees in wind direction. In the case of the opposite direction of the wind, 90, 120 and 140 degree angles were examined. Based on the average of the 25% of the results of the surveys, it was possible to determine the dimensions of sailing equipment that could be considered useful for all wind conditions between 9 and 20 m in length. In addition, estimation of boat speed, drift force and heel angle performance values of the desired length of the vessel is provided with an error rate of less than 2%.
Keywords: Sailing Yachts; Sail Parameters; Systematic Sailing Analysis; Engineering; Transportation